2D Functional Systems: Recent Advances in the Functional 2D Photonic and Optoelectronic Devices (Advanced Optical Materials 3/2019). Issue 3 (4th February 2019) - Wang, Xiaoting; Cui, Yu; Li, Tao; Lei, Ming; Li, Jingbo; Wei, Zhongming
Abstract : Recently various functional systems based on two‐dimensional layered materials have been developed with novel photonic and optoelectronic properties. Beyond the fast speed, high efficiency or sensitivity, these 2D crystals can offer additional advantages and unique functional applications in terms of spectrum range, polarization, intensity, and structural designs, which are comprehensively discussed in the review paper by Ming Lei, Zhongming Wei and co‐workers (article number1801274 ). The advantages are discussed for long‐wavelength photodetector, 2D polarization‐sensitive photodetector, 2D optoelectronic memory, and 2D material‐based optical modulator.